2021
DOI: 10.3389/fneur.2021.639994
|View full text |Cite
|
Sign up to set email alerts
|

From Genotype to Phenotype: Expanding the Clinical Spectrum of CACNA1A Variants in the Era of Next Generation Sequencing

Abstract: Ion channel dysfunction is a key pathological substrate of episodic neurological disorders. A classical gene associated to paroxysmal movement disorders is CACNA1A, which codes for the pore-forming subunit of the neuronal calcium channel P/Q. Non-polyglutamine CACNA1A variants underlie familial hemiplegic ataxia type 1 (FHM1) and episodic ataxia type 2 (EA2). Classical paroxysmal manifestations of FHM1 are migraine attacks preceded by motor aura consisting of hemiparesis, aphasia, and disturbances of conscious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 118 publications
2
48
0
4
Order By: Relevance
“…Previous studies suggested that gain-of-function FHM1 mutations were associated with increased susceptibility to CSD. However, a recent study reported a de novo CACNA1A mutation causing hemiplegic migraine and developmental delay but without epilepsy, revealing a loss-of-function of Ca v 2.1 channel [ 38 ]. This confirmed that different functional consequences may occur in patients with intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that gain-of-function FHM1 mutations were associated with increased susceptibility to CSD. However, a recent study reported a de novo CACNA1A mutation causing hemiplegic migraine and developmental delay but without epilepsy, revealing a loss-of-function of Ca v 2.1 channel [ 38 ]. This confirmed that different functional consequences may occur in patients with intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…This patient's clinical picture is most consistent with paroxysmal kinesigenic dyskinesia, as she has attacks of dystonia that are triggered by voluntary movement, last from a few seconds to a minute, and are relieved with rest [ 8 ]. Her paroxysmal dystonia is likely due to her mutation in CACNA1A , as it is sometimes seen during episodes of ataxia in EA2 [ 9 ], there are other case reports of CACNA1A mutations being associated with dystonia, and CACNA1A knockout mice (Ca V 2.1 −/− ) exhibit dystonia and cerebellar atrophy [ 3 ]. Dystonia, usually cervical, can occur in EA2 during paroxysmal episodes of ataxia and can become chronic if secondarily progressive ataxia develops.…”
Section: Discussionmentioning
confidence: 99%
“…Dystonia, usually cervical, can occur in EA2 during paroxysmal episodes of ataxia and can become chronic if secondarily progressive ataxia develops. There have also been case reports of patients with EA2 who went on to develop interictal dystonia later in their disease course [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CACNA1A disease spectrum encompasses a number of autosomal-dominant allelic disorders, which feature a various combination of episodic and chronic neurological signs [1]. Episodic manifestations include migraine with hemiplegic aura, attacks of paroxysmal ataxia, paroxysmal dystonia and epilepsy [1]. Chronic neurological symptoms consist of various degree of cerebellar ataxia, developmental delay, cognitive and psychiatric symptoms [1].…”
Section: Introductionmentioning
confidence: 99%